نقد النقد في الثقافة المعاصرة. قراءة في مشروع عبد العزيز حمودة - بن محمد, اللقاني; بالقاسم, محمد (جامعة الوادي - University of Eloued, 2020)
تسعى الدراسة لإثبات وجود لبنات في تاريخ البلاغة العربية تكفي لتكوين نظرية لغوية وأدبية نستطيع من خلالها إقامة المقارنات بين كثير من القضايا التي انشغل بها علم اللغة الحديث. وسؤال الدراسة:من خلال ثلاثية حمودة، هل أفرز العقل العربي أثناء العصر الذهبي للبلاغة العربية أركان نظرية لغوية وأدبية؟. ومنهج الدراسة وصفي تحليلي، كما ساعدنا المنهج التاريخي المقارن إذ نصف الظاهرة ونحلل مختلف الأفكار، كما نسرد النظريات البلاغية ونقارنها بالدراسات النقدية الحديثة. وتوصل البحث إلى عدة نقاط من أبرزها أنه قد آن الأوان للنهوض بمشروع عربي إسلامي للخروج من حالة التيه عن طريق رأب الشرخ الحضاري وإقرار الهوية الثقافية. The current papers aims at creating a linguistic and a literary theory in the Arab world, resorting to great figures in Arabic Rhetoric. An approach that allows for a comparison amongst many modern linguistic issues. The study is based is on Hmouda's critical approach; have the Arab world in the golden rhetoric age been able to come up with a genesis of a linguistic and a literary theory. The study uses descriptive and analytic approaches. Comparative history has ales been helpful as we account for the history and analysis of the approach and we compare it to other approaches. The study drew the conclusion that it is high time we formed a theory of our own, of Arab and Islam breeding, so as to break free from the state of loss by connecting to our history and resorting to our cultural identity.
مقال
Keywords: نظرية ; لغوية ; أدبية ; عبد العزيز حمودة ; نقد